METHODOLOGY OF STUDENT INDEPENDENT EDUCATION IN THE KPEDIT-MODULE SYSTEM - Khaitova Shakhnoza Daniyarovna; Nurmukhamdieva Lola Alisherovna (Journals Park Publishing, 2023)
This article describes the role and importance of independent education in the credit module system, the main component of the pedagogical process of activating students’ independent education.
Keywords: Independent education, activation, pedagogical process, pedagogical system, pedagogical process, innovative approach. mobile technology.